Irisin attenuates H(2)O(2)-induced apoptosis in cardiomyocytes via microRNA-19b/AKT/mTOR signaling pathway - Peng, Qing (Int J Clin Exp Pathol, 2017)
Irisin, a novel muscle-secreted peptide, has been proposed to play a potential role in improving myocardial remodeling that leads to impaired myocardial function and heart failure. It has been reported that controlling reactive oxygen species (ROS) exposure could increase cardiomyocyte survival and prevent pathological remodeling of the myocardium. Therefore, we aimed to determine the potential protective effects of Irisin pretreatment against ROS in cardiomyocytes and explored the potential mechanisms. H9c2 cells that were subjected to H(2)O(2) in vitro were used to mimic myocardial remodeling. Then, the effects of Irisin on myocardial cell proliferation, apoptosis and cellular ROS levels were evaluated during this process by using MTT assay, flow cytometry analysis and 2’7’-Dichloro fluoresc in diacetate (DCFH-DA). In order to determine whether Irisin could regulate any microRNA (miRNA) during this process, six miRNAs that are known to be involved in apoptosis of cardiomyocytes were assessed by qRT-PCR. The protective effects of Irisin on cardiomyocytes mediated by miR-19b were evaluated by detecting cell proliferation and apoptosis. In addition, the potential target of miR-19b was predicted with bioinformatics tools and verified using dual-luciferase reporter assay. Finally, the protein levels of members of the phosphatidylinositol 3-kinase (PI3K)/Akt/signaling pathway were also examined by Western Blot. Our study showed that Irisin treatment improved H(2)O(2)-induced cell viability and attenuated the levels of intracellular ROS and the apoptosis of cardiomyocytes in a dose-dependent manner. We also demonstrated that Irisin promoted cell viability and inhibited cell apoptosis via upregulating miR-19b expression. In addition, PTEN was identified as a functional target gene of miR-19b that was responsible for its anti-apoptotic effects in cardiomyocytes. Further study demonstrated that Irisin-regulated miR-19b could reactivate the AKT/mTOR signaling pathway blocked by H(2)O(2) in H9c2 cells. We demonstrated that Irisin strongly enhances cellular proliferation and preventsapoptosis of cardiomyocytes as well as attenuates the levels of intracellular ROS induced by H(2)O(2). These effects might be mediated through the miR-19b/AKT/mTOR signaling pathway, which provide a new insight into the mechanism by which Irisin may have beneficial effect on myocardial remodeling.